If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-7=12+42x
We move all terms to the left:
4x-7-(12+42x)=0
We add all the numbers together, and all the variables
4x-(42x+12)-7=0
We get rid of parentheses
4x-42x-12-7=0
We add all the numbers together, and all the variables
-38x-19=0
We move all terms containing x to the left, all other terms to the right
-38x=19
x=19/-38
x=-1/2
| b÷18=-6 | | (x-5)^2=49 | | -6x/30=18 | | 2x+(1/4)=3x+(3/4) | | (5)/x=9/8x+1 | | X²-x+3=0 | | 7=32÷(5x-3) | | 2(b+5)=12 | | 3(2x+1)=3+2(2x+5) | | 10-2x+x-5=3x-9+3x | | 40+x=3x+2x+12 | | 3x-15=-9+7x-5 | | 3x2-15=-x2+21 | | 16-3(4-2)=x | | z-11=-9 | | (x-1)^2-20=0 | | 13x=2x+55 | | 19-x=1 | | h=100100h+6h+3h | | 7-5a=3a-17 | | x-11+4x=2+x=9+3x-5=0 | | x+6/26=1 | | 8x-2(x+1)=2(3x-1 | | 1/5(2x+94)=5x | | 3x2-4=71 | | 3x+7+x-3+7x-4+3x+5+2x-9=540 | | h2=9/100 | | 2y^2-4=y^2 | | x-(-11)=0 | | c=9/100 | | 6/x-1=9/6 | | 9=7x+1-6 |